Exploring MR regression patterns in rectal cancer during neoadjuvant radiochemotherapy with daily T2- and diffusion-weighted MRI - Bostel, Tilman; Dreher, Constantin; Wollschläger, Daniel; Mayer, A.; König, Franz; Bickelhaupt, Sebastian; Schlemmer, Heinz-Peter; Huber, Peter E.; Sterzing, Florian; Bäumer, Philipp; Debus, Jürgen; Nicolay, Nils (Radiation oncology, 2020)
To date, only limited magnetic resonance imaging (MRI) data are available concerning tumor regression during neoadjuvant radiochemotherapy (RCT) of rectal cancer patients, which is a prerequisite for adaptive radiotherapy (RT) concepts. This exploratory study prospectively evaluated daily fractional MRI during neoadjuvant treatment to analyze the predictive value of MR biomarkers for treatment response.
Gesehen am 03.09.2020